2022
DOI: 10.3390/ijms24010167
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9-Induced Inactivation of the Autism-Risk Gene setd5 Leads to Social Impairments in Zebrafish

Abstract: Haploinsufficiency of the SETD5 gene, encoding a SET domain-containing histone methyltransferase, has been identified as a cause of intellectual disability and Autism Spectrum Disorder (ASD). Recently, the zebrafish has emerged as a valuable model to study neurodevelopmental disorders because of its genetic tractability, robust behavioral traits and amenability to high-throughput drug screening. To model human SETD5 haploinsufficiency, we generated zebrafish setd5 mutants using the CRISPR/Cas9 technology and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
0
0
Order By: Relevance
“…ISH on frozen tissue sections was performed as described in Gabellini et al [25], with some modifications. Cryosections were thawed and washed in PBT (PBS + 0.5% Triton X-100) and incubated with either 300 ng/mL prr21a-201 or prr12b-201 antisense probes at 65 • C O/N.…”
Section: Ish On Adult Brain Cryosectionsmentioning
confidence: 99%
“…ISH on frozen tissue sections was performed as described in Gabellini et al [25], with some modifications. Cryosections were thawed and washed in PBT (PBS + 0.5% Triton X-100) and incubated with either 300 ng/mL prr21a-201 or prr12b-201 antisense probes at 65 • C O/N.…”
Section: Ish On Adult Brain Cryosectionsmentioning
confidence: 99%
“…ENU (N-ethyl-N-nitrosourea) mutagenesis has been utilized to generate knockdown models of FMR1 [252], resulting in zebrafish with ASD-like behavior [157]. Other monogenic zebrafish models of ASD involve the knockout of arid1b [253], chd8 [254], shank3b [64], mecp2 [255], and setd5 [256], among others. Importantly, the monogenic nature of zebrafish models of ASD does not fully recapitulate the environmental influences or the typically polygenic nature of ASD in humans; however, it can provide a simplistic and targeted approach to studying the effects of different therapeutic modalities in reducing the ASD phenotype under specific conditions.…”
Section: Autism Spectrum Disordersmentioning
confidence: 99%
“…Few attempts at rescuing autistic-like phenotypes were performed using compounds administered through simple water immersion. Gabellini et al showed that bath immer-sion with risperidone rescued social interest behaviors in setd5 knockout zebrafish [256]. Rahmati-Holasoo et al found that bath immersion with oxytocin provided neuroprotective effects and improved social behaviors in a valproic acid-induced ASD model of zebrafish larvae [260].…”
Section: Autism Spectrum Disordersmentioning
confidence: 99%